2017
DOI: 10.5334/pia-481
|View full text |Cite
|
Sign up to set email alerts
|

Shells and Humans: Molluscs and Other Coastal Resources from the Earliest Human Occupations at the Mesolithic Shell Midden of El Mazo (Asturias, Northern Spain)

Abstract: Human populations exploited coastal areas with intensity during the Mesolithic in Atlantic Europe, resulting in the accumulation of large shell middens. Northern Spain is one of the most prolific regions, and especially the so-called Asturian area. Large accumulations of shellfish led some scholars to propose the existence of intensification in the exploitation of coastal resources in the region during the Mesolithic. In this paper, shell remains (molluscs, crustaceans and echinoderms) from stratigraphic units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…194,500 (unit 114) and 184,900 (unit 115), more than twice the 91,636 found in unit 108 (173,174). Site structure may explain the deviation, at least in part, as the samples come from a peripheral area of the site and reflect how dense shell can be in well-preserved refuse dumps; if post-depositional processes had resulted in their scattering across the 100 m² of El Mazo's sheltered area, the overall density of the remains would have been averaged out and, at any given point of sampling, much lower (and the attendant breakage would make for significantly diminished specimen counts).…”
Section: S101 Comparison With Holocene Shell-middensmentioning
confidence: 81%
“…194,500 (unit 114) and 184,900 (unit 115), more than twice the 91,636 found in unit 108 (173,174). Site structure may explain the deviation, at least in part, as the samples come from a peripheral area of the site and reflect how dense shell can be in well-preserved refuse dumps; if post-depositional processes had resulted in their scattering across the 100 m² of El Mazo's sheltered area, the overall density of the remains would have been averaged out and, at any given point of sampling, much lower (and the attendant breakage would make for significantly diminished specimen counts).…”
Section: S101 Comparison With Holocene Shell-middensmentioning
confidence: 81%
“…The more abundant species adapted to cold water, such as the periwinkle Littorina littorea (Linnaeus, 1758) and the limpet Patella vulgata (Linnaeus, 1758) in the late Pleistocene, were replaced by species better suited to warmer conditions such as P. lineatus, Patella depressa Pennant, 1777, and P. ulyssiponensis in the Holocene [81,82]. A similar pattern is visible today in the Cantabrian coast, with a predominance of warmer species such as P. lineatus and the absence of L. littorea [53].…”
Section: Climate Change Effects On Intertidal Communities: Impacts Onmentioning
confidence: 86%
“…Hunter-gatherers have exploited intertidal grazers, since prehistoric times, and there are evidences that the densities and the maximum sizes of several species were reduced by the exploitation [51,52]. Studies performed in Northern Spain showed that topshells and limpets were collected, at subsistence exploitation levels, from intertidal areas of exposed shores, leading to the formation of huge shell middens [53]. In fact, intertidal resources have always been collected by humans as food supplement or used as a bargaining chip with other products worldwide [54,55].…”
Section: Harvestingmentioning
confidence: 99%
“…Elemental ratios in P. vulgata marine mollusc shells are typically measured in the calcite m+2 shell layer [9,36,37], because that part of the shell covers most of the mollusc's lifespan with high shell deposition rates, resulting in a long section that enables high temporal resolution measurements. The m-2 calcite layer located near the P. vulgata shell apex is now shown to preserve the same Mg/Ca record [25], but is compressed into a thickness of only a few millimetres.…”
Section: Libs Mg/ca Profiles Measured In the P Vulgata Shell Apex Areamentioning
confidence: 99%